1998
DOI: 10.1126/science.281.5375.419
|View full text |Cite
|
Sign up to set email alerts
|

Corelease of Two Fast Neurotransmitters at a Central Synapse

Abstract: It is widely accepted that individual neurons in the central nervous system release only a single fast transmitter. The possibility of corelease of fast neurotransmitters was examined by making paired recordings from synaptically connected neurons in spinal cord slices. Unitary inhibitory postsynaptic currents generated at interneuron-motoneuron synapses consisted of a strychnine-sensitive, glycine receptor-mediated component and a bicuculline-sensitive, gamma-aminobutyric acid (GABA)A receptor-mediated compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
601
6
10

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 749 publications
(656 citation statements)
references
References 32 publications
39
601
6
10
Order By: Relevance
“…Both antagonists at high enough concentrations will cross-react with the other receptor. However the concentrations used to isolate mIPSCs and sIPSCs in the present study are below those at which appreciable crossover block occurs (Jonas et al, 1998). In that study glycine was the dominant contributor to evoked IPSCs, with faster kinetics than GABAergic currents.…”
Section: Spontaneous Inhibitionmentioning
confidence: 58%
See 1 more Smart Citation
“…Both antagonists at high enough concentrations will cross-react with the other receptor. However the concentrations used to isolate mIPSCs and sIPSCs in the present study are below those at which appreciable crossover block occurs (Jonas et al, 1998). In that study glycine was the dominant contributor to evoked IPSCs, with faster kinetics than GABAergic currents.…”
Section: Spontaneous Inhibitionmentioning
confidence: 58%
“…In the glycine pu experiments, unlike the experiments on release, bicuculline concentrations were in the range in which some crossover block of glycine receptors is observed (Jonas et al, 1998); however this should not have a ected anaesthetic actions on the remaining glycine currents. In some neurons amplitudes were decreased, although the decrease was signi®cant only for sIPSCs in the presence of en¯urane.…”
Section: Anaesthetic Actions: Postsynapticmentioning
confidence: 93%
“…Like other examples of cotransmission (23,24), the functional consequences of having two transmitters at central spinal synapses are not completely clear. Activity in central MN synapses generate negative (MN-RC-MN) and positive (MN-MN) feedback loops that in turn regulate MN activity.…”
Section: Discussionmentioning
confidence: 95%
“…ten Bruggencate and Sonnhof (1972) demonstrated that iontophoretic application of glycine and GABA generates IPSPs in hypoglossal motoneurons, and this hyperpolarization can be blocked by glycine and GABA antagonists, strychnine and picrotoxin, respectively. Studies using intracellular recording in rodent in vitro preparation showed that glycine and GABA are either colocalized and coreleased from the same presynaptic vesicle or released from the separate terminals onto spinal and cranial motoneurons (Jonas et al, 1998;O'Brien and Berger, 1999;Russier et al, 2002). Anatomical studies also demonstrated that input terminals on spinal motoneurons contain GABA, glycine, or both (Taal and Holstege, 1994;Ornung et al, 1996).…”
Section: Discussionmentioning
confidence: 99%